2013
DOI: 10.1371/journal.pone.0077082
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal Abdominal Diameter Is an Independent Predictor of All-Cause and Cardiovascular Mortality in Incident Peritoneal Dialysis Patients

Abstract: Backgrounds and AimsVisceral fat has a crucial role in the development and progression of cardiovascular disease, the major cause of death in end-stage renal disease (ESRD). Although sagittal abdominal diameter (SAD), as an index of visceral fat, significantly correlated with mortality in the general population, the impact of SAD on clinical outcomes has never been explored in ESRD patients. Therefore, we sought to elucidate the prognostic value of SAD in incident peritoneal dialysis (PD) patients.MethodsWe pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…One prospective, population-based study of adults demonstrated that SAD contributed significantly to the prediction of incident diabetes in models including BMI [41], and a longitudinal study of patients with type 2 diabetes reported that SAD was superior to waist circumference or BMI for predicting incident cardiovascular events [42]. Other studies have documented associations between SAD and mortality in selected, high-risk populations [43,44]. …”
Section: Discussionmentioning
confidence: 99%
“…One prospective, population-based study of adults demonstrated that SAD contributed significantly to the prediction of incident diabetes in models including BMI [41], and a longitudinal study of patients with type 2 diabetes reported that SAD was superior to waist circumference or BMI for predicting incident cardiovascular events [42]. Other studies have documented associations between SAD and mortality in selected, high-risk populations [43,44]. …”
Section: Discussionmentioning
confidence: 99%
“…Most identified causes of sudden natural death ( n = 54) were aortic diseases ( n = 30). Others suggested that in individuals without a definite radiologically identified cause of sudden natural death it was due to coronary artery disease and numerous studies found an association between abdominal adiposity and cardiovascular disease . The cellular lipid content determines the size of adipocytes; large, mature adipoctyes were filled almost entirely by large lipid droplets .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used anthropometric data from the US National Health and Nutrition Examination Survey (NHANES) to address: 1) Sex differences in SAD in the entire population as well as in the subgroups characterized by age, race/ethnicity, education, birth place, and household income; 2) Sex differences in socio-economic correlates of SAD. Considering the important role of sex in cardiovascular diseases 16 and the important role of SAD in obesity-related health risks, [5][6][7][8][9] our ndings will provide useful insights for investigating cardiometabolic risk separately in men and women.…”
Section: Introductionmentioning
confidence: 94%
“…4,5 SAD has beeen linked to increased risks of cardiometabolic disorders [5][6][7] and mortality. 8,9 Women are reported to have lower intra-abdominal/visceral adiposity than men while the difference is diminished and not consistently seen in the elderly [10][11][12] . It remains relatively unknown whether SAD, as a manifest measure of visceral adiposity, differs by sex in the general population and in the subgroups de ned by socio-economic characteristics.…”
Section: Introductionmentioning
confidence: 99%